Emotional intelligence and quality of nursing care: A need for continuous professional development - Elmira Khademi; Mohammad Abdi; Mohammad Saeidi; Shahram Piri; Robab Mohammadian (Wolters Kluwer Medknow Publications, 2021)
Background: Emotional Intelligence (EI) is necessary for personal and professional success. This study aimed to determine the relationship between EI and quality of nursing care from the viewpoint of nurses and patients. Materials and Methods: This descriptive correlational study was conducted using convenience sampling to select the patients (n = 300) and census sampling to select the nurses (n = 100) at Amir Alam Hospital in Tabriz, Iran, in 2018. The data collection tools were the Quality Patient Care Scale (QUALPAC) and EI test by Bradberry-Greaves. Data analysis was performed in SPSS Version 20, using t-test, ANOVA, Chi-square, Pearson's correlation test, and multivariate analysis. Results: The mean (SD) score of EI was 91.17 (12.33) in nurses, and the mean (SD) score of nursing care quality was 184.01 (37.41) and 202.22 (22.30) from the viewpoint of patients and nurses, respectively. There was no significant difference between the two viewpoints (p = 0.652). However, there was a significant correlation between the nurses' EI and quality of nursing care (r = 1.00, p < 0.001). The educational level was the strongest predictor of increase in nursing care quality from the patients' viewpoint, according to the multivariate analysis (β = −0.27, p < 0.001). Conclusions: EI positively affects the quality of nursing care and its dimensions. Therefore, it is recommended that nursing policymakers consider educational programs to strengthen the nurses' EI and enhance the quality of nursing care. Patients, similar to nurses, can be proper indicators of the quality of nursing care; accordingly, simultaneous use of these indicators is suggested.